Developing a cross-organisational physiotherapy-specific critical care competency framework to enable collaborative working: an overview of the integration journey across an academic health science centre - Claire Bradley; Linda Eftychiou; Laura Mylott; Kirsty Jerrard; Debbie McKenzie; Kelly Morris; Charlotte Pereira; Claire Purkiss; Leyla Osman; Charles C. Reilly (BMC Health Services Research)
Abstract Background Competency frameworks are commonly used to define expectations, aid acquisition of appropriate skills and ensure safe delivery of care to patients. The Intensive Care Society’s Allied Health Professionals Critical Care Professional Development Framework (CCPDF) provides broad descriptors of levels of practice ranging from novice to expert. Prior to May 2021, no standardised clinical competency frameworks governed physiotherapy practice or development in the critical care setting in the UK. Methods The aim was to develop and evaluate the value of a cross-organisational, physiotherapy-specific, critical care competency framework to enable collaborative working in a partnership comprising of three previously independent NHS foundation trusts across six sites within an academic health science centre. Between May and November 2021, a pragmatic approach following the first three stages of Whiddett and Hollyforde’s process for developing a tailored competency framework was used: 1) preparation, 2) information collection and 3) compiling the framework and validation. Results Following analysis of key documents and through comprehensive engagement, a proposed competency framework was agreed upon, reflecting levels from Foundation to Expert. Competencies were categorised into eight areas: Anatomy and Physiology, Assessment, Laboratory and Pharmacy, Respiratory Support, Airway Clearance Techniques, Tracheostomy, Rehabilitation, and Communication, Documentation, and Teamwork. A survey was sent to 112 staff with a 39% response rate. Most respondents said the framework would support improvement in patient care and staff development, with time and staffing being barriers to use. An online format was preferred. Conclusion The final document was called Kings Health Partners Physiotherapy Critical Care PROSPECTS (PROfession SPecific Excpectations, CompeTencies and Skills) Framework. It was valued by users as a self-assessment document and tool for career development and learning opportunities. Future work will focus on piloting the framework and developing associated learning resources.